Estimation of Water-Use Efficiency Based on Satellite for the Typical Croplands - Tongxin Wang; Hongyan Zhang; Zhao Jianjun; Xiaoyi Guo; Shouzheng Tong (IEEE Access, 2020)
Water resources become scarce due to the melting of glaciers caused by climate change, and water pollution caused by human activities and overuse of freshwater resources are aggravating this phenomenon. Cropland is an essential part of the terrestrial ecosystem, and it is of great importance to make rational use of the limited water resources to have higher water use efficiency (WUE). The quantitative estimation of the ecosystem WUE and tracking its dynamics of croplands is crucial for addressing the impact of future climate change on crop production. Scaling up field observations of flux towers to a large scale remains a challenge and there are few reports on estimating WUE directly from remote sensing data. This study examined the main environmental factors that contribute to changes in WUE of typical crops, and found that the EVI showed strong correlation with the ecosystem WUE of typical croplands, which can be developed to track ecosystem WUE. This study proposed an alternative method exclusively based on MODIS EVI data analysis with an R2 of nearly 0.90 and a small RMSE, which was much better than the calculations of the MODIS GPP and ET products, and provided an accessible method for modelling the ecosystem WUE to effectively manage water use in croplands.